Who wants to farm? Answers depend on how you ask: A case study on youth aspirations in Kenya - LaRue, Katie; Daum, Thomas; Mausch, Kai; Harris, Dave (Springer, 2021)
While there is a consensus that rural poverty has to be reduced, there are two opposing views on the role that agriculture can play in this regard: a “farm-based” and an “off-farm led” development paradigm where the respective other sector is merely a complementary income source during a transition period. The latter paradigm is supported by studies finding that rural youth in sub-Saharan Africa are not particularly interested in agriculture. However, policy discourse on youth in agriculture often situates their aspirations as either full-time farming or non-farming, thus either supporting or opposing one or the other of the two paradigms, while neglecting the shades of grey between these two extremes. Using a mixed-methods approach—a household survey and a narrative-based tool called SenseMaker—to collect data from both adults and youth in 261 households in rural Kenya, this study suggests that this categorical understanding needs to be revisited to inform rural development strategies based on the actual aspirations of rural youth.